2019
DOI: 10.1021/acsaem.8b02158
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Treated Defect-Rich W18O49 Nanowire-Modified Graphite Felt as High-Performance Electrode for Vanadium Redox Flow Battery

Abstract: To improve the electrochemical performance of graphite felt (GF) electrodes in vanadium redox flow batteries (VRFBs), we synthesized simple, inexpensive, and conductive W18O49 nanowires (W18O49NWs) as electrocatalysts on the surface of GF through the one-step solvothermal process. Cyclic voltammetry and electrochemical impedance spectroscopy studies revealed that W18O49NWs exhibit electrocatalytic effects on a VO2 +/VO2+ redox couple on the positive side, which enhance the electrochemical kinetics of the redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 67 publications
0
54
0
Order By: Relevance
“…Previous studies have demonstrated that oxygen vacancies (V O ) can be generated in metal oxides under oxygen-reduced conditions resulting in changes to the electronic structure and powder appearance. 5 , 9 , 12 , 31 , 37 Therefore, to verify that visual changes are not due to the formation of V O , the binding environment of O in SNO NPs was probed ( Figure 3 a). The deconvoluted O 1s XPS spectra of as-synthesized NPs identifies four peaks assigned to SrNbO 3 lattice oxygen (529.2 eV), Sr 0.7 NbO 3−δ′ lattice oxygen (530.0 eV), oxygen defects (531.5 eV), and surface hydroxyls (532.6 eV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that oxygen vacancies (V O ) can be generated in metal oxides under oxygen-reduced conditions resulting in changes to the electronic structure and powder appearance. 5 , 9 , 12 , 31 , 37 Therefore, to verify that visual changes are not due to the formation of V O , the binding environment of O in SNO NPs was probed ( Figure 3 a). The deconvoluted O 1s XPS spectra of as-synthesized NPs identifies four peaks assigned to SrNbO 3 lattice oxygen (529.2 eV), Sr 0.7 NbO 3−δ′ lattice oxygen (530.0 eV), oxygen defects (531.5 eV), and surface hydroxyls (532.6 eV).…”
Section: Resultsmentioning
confidence: 99%
“…EIS spectroscopy was performed to further characterize the electrical activity during the IMT for these NPs. This technique has been used to monitor changes in the electronic conductivity of reduced W 18 O 49 , 5 TiO 2 , 37 and SrTiO 3 . 41 The corresponding Nyquist plots for the reduced SNO NPs are shown in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Bayeh et al [ 107 ] presented a novel approach by synthesizing and evaluating a nonstoichiometric tungsten oxide W 18 O 48 (WO 2.72 ) as a catalyst for the V(IV)/V(V) redox reaction. As reported previously in the literature, [ 165 ] the reduction of WO 3 , which has a perfect crystalline structure with stacked layers of corner‐sharing WO 6 octahedra (see Figure ), to W 18 O 48 nanowires yields a crystalline structure with oxygen‐containing defects that consist of many hexagonal channels.…”
Section: All‐vanadium Rfbmentioning
confidence: 99%
“…Therefore, in order to enhance the electrochemical activity of GF modified with metal oxides, typically a post-annealing process in a reducing atmosphere (containing H 2 gas) is necessary. Because the concentration of oxygen vacancies in the lattice of metal oxides will be increased during the H 2 thermal treatment process to form defect-rich non-stoichiometric metal oxides, a lower resistance of metal oxides for obtaining higher electrochemical activity is found [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%